Is youth smoking responsive to cigarette prices? Evidence from low- and middle-income countries. Issue 6 (7th July 2011) - Kostova, Deliana; Ross, Hana; Blecher, Evan; Markowitz, Sara
Abstract : Objective: To estimate the price elasticity of cigarette demand among youth in low- and middle-income countries (LMIC). Data: The Global Youth Tobacco Survey was used to obtain data on the smoking behaviour of 315 353 adolescents from 17 LMIC. Design: Two-part model of cigarette demand with country fixed effects. The first part estimates the impact of prices on smoking participation while the second part estimates the impact of prices on the number of cigarettes smoked among current smokers. Besides controlling for individual characteristics such as Age, Gender, Parental Smoking and availability of Pocket Money, the authors control for confounding environmental factors such as anti-smoking sentiment, the prevalence of cigarette advertising and anti-tobacco media messAges, and ease of purchasing cigarettes. All countries in this study are represented with at least two observations over time, which allows us to control for unobserved country characteristics and/or policies that may influence smoking patterns within countries. Results: Cigarette price is an important determinant of smoking. The estimated price elasticity of smoking participation is −0.74, and the estimated price elasticity of conditional cigarette demand is approximately −1.37. The total price elasticity of cigarette demand is −2.11, implying that an increase in price of 10% would reduce youth cigarette consumption by 21.1% at the mean.